SAT-348 Primary Hyperparathyroidism Presenting as Acute Necrotizing Pancreatitis and Diabetic Ketoacidosis in Type 2 Diabetes - Knight, John O’Connell (J Endocr Soc, 2020)
INTRODUCTION: The association between diabetic ketoacidosis (DKA) and acute pancreatitis (AP) is well established. Hypercalcemia from primary hyperparathyroidism (PHPT) is a rare cause of AP, accounting for less than one percent of cases. The constellation of PHPT, AP, and DKA as an initial presentation of diabetes is not known. CASE PRESENTATION: A 33-year-old male with minimal prior healthcare contact presented to the ER with acute encephalopathy after three weeks of polyuria and polydipsia, and later abdominal pain, nausea, and vomiting. He was hyperglycemic to 1310 mg/dl with an anion-gap metabolic acidosis (pH 7.12, serum bicarbonate of 7 mEq/L, anion gap of 33) and elevated beta-hydroxybutyrate to greater than 9 mmol/L, and was profoundly dehydrated with hyperosmolarity to 354 mOsm/kg. He was hypercalcemic to 14.0 mg/dl with elevated parathyroid hormone of 260.7 pg/L. CT of the chest, abdomen, and pelvis revealed acute necrotizing pancreatitis. He was treated with insulin, aggressive fluid resuscitation, and supportive measures, with resolution of encephalopathy, DKA, AP, hyperosmolarity, and kidney injury. Calcium and parathyroid hormone remained elevated, with further workup suggesting PHPT as the etiology of his hypercalcemia. DISCUSSION: Associations between PHPT and AP, and between AP and DKA, are established in the literature, but few cases of DKA from hypercalcemia-induced AP have been described. Our patient highlights the importance of the etiologic workup in both DKA and AP, as both carry high mortality and have high rates of recurrence. Further study is needed to better characterize the relationship between DKA, AP, and PHPT to better inform early diagnosis and prevention efforts.